Saying more than goodbye: emotion messages in Adinkra symbols. Issue 4 (2nd October 2018) - Dzokoto, Vivian; Hill, Ashley; Twum-Asante, Maxwell; Hayfron, Aku Edzui
Abstract: Adinkra symbols are a collection of Akan patterns that have significance in the African Diaspora. Aesthetically pleasing, these symbols are used to adorn a variety of items used in everyday life, such as fabric and furniture. Although the Adinkra symbols communicate specific messages about a variety of social behaviours, and expectations about how members of society ought to conduct themselves, the intersection between the meaning of the symbols and social rules about the experience and expression of affect has hitherto not been given much attention in the literature. Our examination of affect-related messages encapsulated within Adinkra symbols showed that they encourage the maintenance of social harmony and conflict avoidance; address expectations about coping with adversity by promoting values of tenacity and hardiness; promote awe and respect of human and spiritual authority, and promote feelings of love, care and security. These messages are instrumental for the regulation of emotion in the Akan society of Ghana, and may have similar cultural significance for the African–American community which recognizes the important of the symbols as their connection to Africa.